Investigation of the inhibition effect of 1,2,3,4,6-pentagalloyl-β-D-glucose on gastric cancer cells based on a network pharmacology approach and experimental validation - Bi, Jing-hui; Jiang, Yu-han; Ye, Shi-jie; Wu, Min-rui; Yi, Yang; Wang, Hong-xun; Wang, Li-mei (Frontiers in Oncology, 2022)
Background Gastric cancer (GC) is ranked as the third leading cause of cancer-related mortality worldwide. 1,2,3,4,6-Pentagalloyl-β-D-glucose (β-PGG) has various pharmacological activities and has been shown to suppress cancer development. However, the mechanism by which β-PGG inhibits gastric cancer has not been elucidated. Objective This study explored the potential targets and mechanism of β-PGG in GC using the network pharmacology approach combined with in-vitro experiments. Methods The PharmMapper software was used to predict the potential targets of β-PGG, and GC-related genes were identified on the GeneCards database. PPI analysis of common genes was performed using the STRING database. The potential regulatory mechanism of β-PGG in GC was explored through Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses. The binding ability of key genes and target proteins was verified by molecular docking. The effects of β-PGG on genes and proteins were evaluated using the CCK-8 assay, cell cycle analysis, apoptosis assay, real-time fluorescence quantification polymerase chain reaction (qRT-PCR), and Western blotting. Results Eight hub genes involved in cell cycle progression and apoptosis were identified. Cancer-related signaling pathways were identified using the Cytoscape tool. Some of those genes were significantly enriched in the p53 signaling pathway. The CCK-8 assay showed that β-PGG inhibited the proliferation of GC cells. Cell cycle and apoptosis experiments revealed that β-PGG induced cell cycle arrest and apoptosis of gastric cancer cells. qRT-PCR and Western blot analysis showed that β-PGG inhibited β-PGG cells by modulating the p53 signaling pathway. Conclusion In the present study, the targets and mechanism of β-PGG in gastric cancer were explored. The results indicate that β-PGG can be used to develop treatments for GC.